(3GdfbhO h GdHfhc h GdGSJKeGQ h GdOQGSGJ GdGbJUGOjIs - (3Lejd aGFb(B, (3JhQs ((3GdbGgQI(B:s (3OGQ GdcJGH GdMOjK(B,s, 2008)
(3jVe fTCI GdfbhO hJWhQgG, GdYedI GdhQbjI, GdESJKeGQ, GdHfhc, GdHfhc GdJLGQjI, GdHfhc GdCNQi, GdHfhc hYedjGJ GdEFJeGf hGdSjGSI GdEbJUGOjI aj GdHfhc GdJLGQjIs
(3HjHdjhZQGajG(B: (3U U(B.242-243s
Keywords: (3GdESJKeGQs; (3GdHfhcs; (3GdfbhOs